British public employment service reform: activating and civilising the precariat?. (1st October 2019) - Fletcher, Del Roy
Abstract : A post-industrial 'precariat' has emerged characterised by social insecurity to which the state's response has been to secure habituation to insecure labour. This article provides new empirical evidence regarding how the precariat encounter and experience the reformed welfare delivery system. It seeks to explore theoretically whether the precariat is being 'activated' and/or 'civilised'. The author finds that the primary role of Jobcentre Plus is to assess whether the unemployed are 'active'. This has been interpreted by Marxist scholars as a class disciplinary project which renders labour more dependent upon precarious work. However, the evidence presented here suggests that an inappropriate white-collar model of support combined with sanctions frequently results in ill-discipline and disentitlement from benefits. Furthermore, support cannot be conceptualised as a 'civilising offensive' because it is not a deliberate and targeted attempt at inculcating 'civilised' behaviour. Moreover, rather than enforcing the norms of civilised behaviour it drives many into destitution and crime.